1991
DOI: 10.1111/j.1476-5381.1991.tb12490.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential release of tumour necrosis factor, platelet activating factor and eicosanoids during endotoxin shock in anaesthetized pigs; protective effects of indomethacin

Abstract: 1 The effects of indomethacin were investigated on haemodynamics, haematological and blood glucose values, and the release of tumour necrosis factor (TNF), platelet activating factor (PAF) and eicosanoids in anaesthetized pigs receiving 5 pgkg-' E. coli lipopolysaccharide (LPS) over 60min into the superior mesenteric artery. The animals were observed for an additional period of 2 h after the termination of LPS infusion.2 Eight of the 17 animals infused with LPS and not treated with indomethacin died within 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…The lipid mediators-eicosanoids and PAF-released by the macrophages and liver sinusoidal endothelial cells have important functions as well (197,230,254,279). Besides the vasoactive functions of these agents (368,369), PGE 1 and PGE 2 inhibit the transcription of TNF-␣ mRNA in macrophages, resulting in a long-term inhibition of TNF-␣ release (175,317,389,458). The last group of products released in response to LPS are the reactive oxygen species.…”
Section: Macrophages and The Response To Lipopolysaccharide And Lipotmentioning
confidence: 99%
“…The lipid mediators-eicosanoids and PAF-released by the macrophages and liver sinusoidal endothelial cells have important functions as well (197,230,254,279). Besides the vasoactive functions of these agents (368,369), PGE 1 and PGE 2 inhibit the transcription of TNF-␣ mRNA in macrophages, resulting in a long-term inhibition of TNF-␣ release (175,317,389,458). The last group of products released in response to LPS are the reactive oxygen species.…”
Section: Macrophages and The Response To Lipopolysaccharide And Lipotmentioning
confidence: 99%
“…Endotoxin was detectable in the plasma of only 1 neonate with a detectable PAF level. In an animal model of endotoxin shock, plasma PAF levels were elevated only within 30 min after an intravenous endotoxin infusion was begun [13]; therefore, the elevated PAF levels we found are unlikely to have been due to prior transient endotoxinemia.…”
Section: Discussionmentioning
confidence: 85%
“…In endotoxic shock, increased circulating endothelin plasma levels were reported in humans (Pittet et al 1991;Weitzberg et al 1991) and other species (Battistini et al 1993;Nakamura et al 1991), probably because of endotoxin stimulation (Gugiura et al 1989) and hypoxia (Shirakami et al 1991). Since it has been reported that the cardiovascular response to endotoxinaemia is partly mediated by eicosanoids (Mozes et al 1991), and that endothelin induces the release of thromboxane A2 and prostacyclin (de Nucci et al 1988), some authors suggest a role for endothelin in endotoxic shock (Battistini et al 1993).…”
Section: Nonvascular Diseasesmentioning
confidence: 98%